Stand by me [videorecording (Blu-Ray)] - Gideon, Raynold; Evans, Bruce A.; Scheinman, Andrew; Reiner, Rob; Wheaton, Wil; Phoenix, River; Feldman, Corey; O'Connell, Jerry, 1974-; Sutherland, Kiefer, 1966- (Columbia Pictures : [Distributed by] Sony Pictures Home Entertainment, 2011)
Four young friends set out on an adventure to find the body of a missing local teenage boy.